Two novel cationic staphylococcal proteins induce IL-2 secretion, proliferation and immunoglobulin synthesis in peripheral blood mononuclear cells (PBMC) of both healthy controls and patients with common variable immunodeficiency (CVID). - Jahreis, A (1995)
Two cationic proteins, a neutral phosphatase (NP-tase) and a 70-kD protein (p70) were isolated from Staphylococcus aureus by ion exchange chromatography. We compared their properties to those of the well established B cell mitogen of whole, fixed Staph. aureus strain Cowan I cells (SAC). Both purified proteins were able to induce immunoglobulin synthesis in PBMC cultures of healthy donors. NP-tase and p70 also induced immunoglobulin synthesis of PBMC from those patients with CVID who were also responsive to SAC plus IL-2 stimulation. Immunoglobulin synthesis in response to NP-tase and to p70 was time- and dose-dependent and could be inhibited by addition of specific antibodies against the proteins. In contrast to SAC, no addition of exogenous IL-2 was necessary to obtain maximal immunoglobulin synthesis induced by NP-tase or p70. However, neither protein was able to induce immunoglobulin synthesis in B cell-enriched cultures. High amounts of IL-2 were found in supernatants of PBMC from healthy donors following stimulation with low concentrations of NP-tase or p70, and this was associated with vigorous lymphocyte proliferation. Both proteins behave like typical antigens, and not like lectins or superantigens, since an NP-tase-stimulated T cell line showed an antigen-specific, MHC-restricted secondary response. In addition, no preferential T cell receptor V beta chain usage was found with eight V beta-specific MoAb. It is likely that the two proteins induce antigen-specific T cell activation, which is then followed by polyclonal activation of B cells via CD40 receptors and cytokine release.